Utilização de resíduos de rochas ornamentais na produção de cerâmica branca - Dantas, Antônio de Pádua Arlindo (2009)
The marble and granite waste come from the process of mining of those ornamental rocks for use in the building industry. Brazil is one of the largest producers of blocks or finished products of ornamental rocks, extracting about 5.2 tons / year. The largest national producers are the states of Espírito Santo, Minas Gerais and Bahia which account for 80% of the Brazilian production. However, the waste total amount during processing of these blocks reaches 40% of the total. The use of the waste produced by this industry in white ceramics could be a form of disposition, because these materials, are thrownasa mud directly at decantation ponds, wastelands or in rivers, without any treatment. The present work has as main purpose to study the influence that reject of the ornamental rocks on the physical and mechanical properties of white ceramics. X-Ray characterizations of raw materials by were performed X-Ray fluorescence, X-Ray diffraction, granulometric, thermogravimetric and thermodiferencial analysis, five formulations were made (0, 10, 20, 30, 40% in granite weight) wich were burned at three temperatures: 1100°C, 1150°C and 1200ºC with 60 minutes of sorling time. After sintering, the samples were submitted to different analyser absorption of water, linear retraction, apparent porosity, apparent specific mass, flexival stronght, and scanning were obtained microscopy. Compatible technological properties within the limits demanded for the production of porcelainized stoneware